Hubungan antara Penggunaan Aplikasi Quizlet dengan Penguasaan Mufradat Bahasa Arab Siswa Kelas VIII SMPI Al Hidayah Tangerang - Afrina, Dinda; Moh. Aman; Nikmatullah Husni (INTIFA: Journal of Education and Language, 2025)
ABSTRACT   The advancement of digital technology offers great opportunities for the development of learning media, including in Arabic language education. One of the key aspects of mastering Arabic is vocabulary acquisition (mufrodat). This study aims to examine the relationship between the use of the Quizlet application and vocabulary mastery among eighth-grade students at SMPI Al-Hidayah Tangerang. The research employed a quantitative approach with a correlational method. The sample consisted of 25 students selected through a saturated sampling technique. Data were collected using questionnaires to measure the frequency and perception of Quizlet usage and written tests to assess vocabulary mastery. The results of the Pearson Product Moment correlation test revealed a positive and significant relationship between the two variables, with a correlation coefficient of 0.439 and a significance level of 0.028 (p < 0.05). These findings indicate that higher frequency of Quizlet use is associated with better vocabulary mastery. The study recommends the use of digital learning media such as Quizlet as an innovative alternative in Arabic language instruction, particularly to enhance vocabulary acquisition effectively and in line with the learning characteristics of today’s digital-native students. ABSTRAK Kemajuan teknologi digital memberikan peluang besar dalam pengembangan media pembelajaran, termasuk dalam pembelajaran bahasa Arab. Salah satu aspek penting dalam penguasaan bahasa Arab adalah penguasaan mufrodat (kosakata). Penelitian ini bertujuan untuk mengetahui hubungan antara penggunaan aplikasi Quizlet dan penguasaan mufrodat siswa kelas VIII di SMPI Al-Hidayah Tangerang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel terdiri dari 25 siswa yang diambil melalui teknik sampling jenuh. Pengumpulan data dilakukan melalui kuesioner untuk mengukur frekuensi dan persepsi penggunaan Quizlet, serta tes tertulis untuk menilai penguasaan mufrodat. Hasil analisis menggunakan uji korelasi Pearson Product Moment menunjukkan adanya hubungan positif dan signifikan antara kedua variabel, dengan nilai korelasi sebesar 0,439 dan signifikansi 0,028 (p < 0,05). Hasil ini menunjukkan bahwa semakin tinggi intensitas penggunaan Quizlet, semakin baik pula penguasaan mufrodat siswa. Penelitian ini merekomendasikan pemanfaatan media pembelajaran digital seperti Quizlet sebagai alternatif inovatif dalam pembelajaran bahasa Arab, khususnya dalam meningkatkan penguasaan kosakata secara efektif dan sesuai dengan karakteristik peserta didik di era digital.